The Effect of Celebrity Endorsement on Purchase Intention With Brand Awareness as a Mediating Variable on MS GLOW BEAUTY Products (Case Study on MS GLOW BEAUTY Customers at msglowbeauty27 Purwantoro Official Store, Wonogiri) - Hysbrian Maaliki Satria Mukti; Wuryaningsih Dwi Lestari (IECON: International Economics and Business Conference, 2023)
This research aims to determine and analyze whether Celebrity Endorsement has an influence on Purchase Intention, taking into account the factor of Brand Awareness. The method used in this research is a quantitative method. The populationand sample in this research are customers of the msglowbeauty27 store in Purwantoro who have purchased Ms Glow Beauty skincare products, and the number of respondents as the sample in this research is 105 people. The data source used in this research is primary data. The data analysis uses Warp PLS version 7.0. The results of this research conclude that there is a positive influence between Celebrity Endorsement and Purchase Intention. There is a positive influence between Celebrity Endorsement and Brand Awareness. There is a positive influence between Brand Awareness and Purchase Intention. Good Brand Awareness of the Ms Glow Beauty brand will further strengthen the Purchase Intention of the Ms Glow Beauty brand in the minds of consumers.